Unraveling the potential: mRNA therapeutics in oncology - Gawalski, Karol; Przybyszewska, Weronika; Hunia, Jaromir; Gawalska, Alicja; Rymarz, Aleksandra (Frontiers in Oncology, 2025)
Messenger ribonucleic acid (mRNA) technology is a promising platform for cancer immunotherapy. Unlike traditional vaccines that prevent infectious diseases, mRNA’s role in oncology is to stimulate or enhance the immune response against tumor antigens. This review provides an overview of mRNA’s historical development, from its discovery in 1961 to recent clinical trials and Nobel Prize-winning breakthroughs. Therapeutic mRNA flexibility allows the alteration of diverse tumor antigens. Key targets include tumor-associated antigens, which are present on both tumor cells and some healthy cells, as well as tumor-specific antigens unique to cancer cells, such as antiviral antigens and neoantigens arising from tumor mutations. Various approaches to protect mRNA from degradation, including protamine-complexed mRNA, lipoplexes, and lipid nanoparticles, as well as several administration routes, are currently being tested in clinical trials. They are focused on malignancies like melanoma, non-small cell lung cancer, prostate cancer, or pancreatic ductal adenocarcinoma, one of the most challenging cancers. While many trials are in early phases, some have advanced to phase 3 and have shown promising results in both safety and efficacy. However, due to the complexity and heterogeneity of tumors, even among patients presenting the same subgroup of neoplasm, fully universal mRNA-based cancer vaccine seems to be elusive. Personalized mRNA cancer vaccines targeting neoantigens unique to an individual’s tumor have gained traction as a feasible and promising solution. Technological advances in bioinformatics, AI, and machine learning now allow for more accurate identification of immunogenic neoepitopes. The combination this type of therapy with other treatment such as immune checkpoint inhibitors may become one of new solutions in oncology.